Prospecção de fungos quitinolíticos e produção de quitinases por fermentação em estado sólido - Baldoni, Daiana Bortoluzzi (2016)
Fungi are organisms that have high importance as they are the primary decomposers of all terrestrial ecosystems and have critical ecological functions in nutrient cycling and associations with other organisms. Metabolic diversity of fungi aroused great interest for technological research, as new natural products are continually being produced by fungi. However, only a small part of fungal diversity has been grown and selected as biotechnology resource. Much of the potential of fungi is due to the diversity in production of hydrolytic enzymes such as chitinase, which can be used for various purposes. The chitinases hydrolyze the β-1.4 linked in chitin polymer resulting in the release of chito-oligomers. These enzymes are studied for numerous applications such as the production of biopesticides for agriculture use. Despite this relevance, some factors limit a wider commercial use of chitinases such as the lack of organisms with high production rates, high production cost, and low activity and stability of available chitinases. The objectives of this study were to isolate and identify producers of chitinase fungi, evaluate the production of this enzyme in solid state fermentation (SSF), optimize the production of chitinase by largest producer in SSF, evaluate different sources of chitin for the production of chitinase and various solvents for extraction of the enzymes produced during the fermentation process and evaluate the effectiveness of the enzyme extract and biological control in mortality of phytopathogenic nematodes Meloidogyne javanica and M. incognita. 51 fungi were isolated from the exoskeleton of Tibraca limbativentris bugs in 5 collection points distributed in Rio Grande do Sul, Brazil. From the isolated, 50 produced chitinases and ten were selected as the best producers of this enzyme in SSF utilizing wheat bran and macro- and micro-nutrients solution. The ten isolated were identified by ITS1-5.8S-ITS2 nrDNA region. The isolated selected Trichoderma sp. UFSMQ40 with 13.07 U gds-1 of chitinase, followed by the isolated Fusarium sp. UFSMQ32 (11.35 U gds-1), Trichoderma sp. UFSMQ24 (10.11 U gds-1), Fusarium sp. UFSMQ18 (10.05 U gds-1), Fusarium sp. UFSMQ1 (9.84 U gds-1), Lecanicillium sp. UFSMQ6 (971 U gds-1), Fusarium sp. UFSMQ27 (9.11 U gds-1), Fusarium sp. UFSMQ12 (8.92 U gds-1), Fusarium sp. UFSMQ49 (8.16 U gds-1) and Fusarium sp. UFSMQ17 (8.05 U gds-1) showed high production of chitinase in SSF. Subsequently this step, the isolated Trichoderma sp. UFSMQ40 was identified as Trichoderma koningiopsis by amplification of the tef1 gene fragment. As an optimization result the increased production of chitinases by this fungus in SSF was 10.76 U gds-1 and occurred when the wheat bran substrate was used with 55% moisture, 5 g of corn steep liquor, two inoculum disks at 30 °C for 72 h. The colloidal chitin, powders and flakes, should be used as enzyme inducers without altering the production of the chitinase isolated. The use of 75 mL of citrate-phosphate buffer was the best extractor evaluated for the chitinase produced by this isolated in SSF. The Trichoderma koningiopsis UFSMQ40 presents potential for the industrial production of chitinase using agricultural residues as substrates and high nematicide effect against Meloidogyne incognita e Meloidogyne javanica.